2021
DOI: 10.11606/s1518-8787.2021055003614
|View full text |Cite
|
Sign up to set email alerts
|

Pegada de carbono da dieta no Brasil

Abstract: OBJETIVO: Estimar a pegada de carbono da dieta brasileira e de estratos sociodemográficos dessa população. MÉTODOS: A pegada de carbono da dieta foi estimada com base nos dados de dois registros alimentares de 24 horas, obtidos em 2008 e 2009, de uma amostra probabilística da população brasileira com 10 ou mais anos de idade (n = 34.003) e em coeficientes de impacto ambiental de alimentos e preparações culinárias consumidos no Brasil (gCO2e/kg). Médias com intervalos de confiança de 95% do consumo alimentar (k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…Regarding the differences by age group, it was observed that young adults were those with the highest dietary CF and WF, similar to what occurs in other countries such as Brazil [ 37 ] and Sweden [ 34 ]. In our results, the highest socioeconomic level is the one that reports the highest CF and WF, which could be aligned to other national level studies where higher incomes have a greater environmental footprint due to their diet [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Regarding the differences by age group, it was observed that young adults were those with the highest dietary CF and WF, similar to what occurs in other countries such as Brazil [ 37 ] and Sweden [ 34 ]. In our results, the highest socioeconomic level is the one that reports the highest CF and WF, which could be aligned to other national level studies where higher incomes have a greater environmental footprint due to their diet [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 77%
“…The Chilean diet produces 4.67 kg of CO 2eq per person daily, a value 42% higher than what is estimated would generate a nutritionally adequate and ecologically sustainable diet worldwide [ 34 ]. When comparing the Chilean CF with that of other countries, it is observed that it is lower than that of the USA (4.72 Kg CO 2eq ) [ 12 ] and Argentina (5.48 Kg CO 2eq ) [ 35 ] but higher than that of Peru (2.61 Kg CO 2eq ) [ 14 ], France (4.09 Kg CO 2eq ) [ 36 ], Brazil (4.48 Kg CO 2eq ) [ 37 ], and Denmark (4.63 Kg CO 2eq ) [ 13 ], differences produced probably by the high consumption of animal-sourced foods. In addition, the CO 2 emissions generated by the Chilean diet represent 33% of the country’s total GHG emissions [ 38 ], which would be above the estimated average value of CF associated with food systems (20–30%) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the daily consumption frequency was obtained, the values were multiplied by the per capita amount to obtain the estimated food consumption (EFC), as described in Equation (1) [ 28 , 40 ]: …”
Section: Methodsmentioning
confidence: 99%
“…To obtain the final footprint of each individual, the environmental footprint values calculated from all food groups consumed were added up, as shown in Equation (2) [ 23 , 28 ]: where i is each food group consumed and “Food groups consumed” is the total amount of groups present in the PQ, considering the consumption informed by the individual. The EFC i refers to the EFC of each food group (Equation (1)), while impact refers to the environmental footprint values for each group according to the type of footprint.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation